2021
DOI: 10.32553/ijmbs.v5i1.1618
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of C-Reactive Protein GCF Level in Periodontitis Patients After Scaling and Root Planing With and Without Diode Laser

Abstract: Background and Objectives: C?reactive protein (CRP) is a type I acute phase reactant. A number of studies have reported elevated gingival crevicular fluid (GCF) CRP levels in periodontitis subjects, which decrease following periodontal therapy. Effect of diode laser as an adjuct to Scaling & Root planing is also well stablished. The aim of the present study was to evaluate the effect of periodontal treatment SRP with diode laser, on CRP levels in GCF in patients with chronic periodontitis. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Furthermore, the findings of the study supported the hypothesis that the levels of GCF biomarkers are related to the degree of inflammation, collagen degradation and bone turnover. 28 In another study, both scaling and root planing (SRP) alone and using a diode laser as an adjunct showed a reduction in the serum CRP levels, 29 which is in agreement with the results of the present study. A study by Jayaprakash et al reported that the CRP levels in GCF gradually increased from a healthy periodontium to gingivitis, and further increased in periodontitis.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the findings of the study supported the hypothesis that the levels of GCF biomarkers are related to the degree of inflammation, collagen degradation and bone turnover. 28 In another study, both scaling and root planing (SRP) alone and using a diode laser as an adjunct showed a reduction in the serum CRP levels, 29 which is in agreement with the results of the present study. A study by Jayaprakash et al reported that the CRP levels in GCF gradually increased from a healthy periodontium to gingivitis, and further increased in periodontitis.…”
Section: Discussionsupporting
confidence: 90%